Hearing Rehabilitation With a Chat-Based Mobile Auditory Training Program in Experienced Hearing Aid Users: Prospective Randomized Controlled Study - Jae Sang Han; Ji Hyung Lim; Yeonji Kim; Aynur Aliyeva; Jae-Hyun Seo; Jaehyuk Lee; Shi Nae Park (JMIR mHealth and uHealth, 2024)
Abstract BackgroundHearing rehabilitation with auditory training (AT) is necessary to improve speech perception ability in patients with hearing loss. However, face-to-face AT has not been widely implemented due to its high cost and personnel requirements. Therefore, there is a need for the development of a patient-friendly, mobile-based AT program. ObjectiveIn this study, we evaluated the effectiveness of hearing rehabilitation with our chat-based mobile AT (CMAT) program for speech perception performance among experienced hearing aid (HA) users. MethodsA total of 42 adult patients with hearing loss who had worn bilateral HAs for more than 3 months were enrolled and randomly allocated to the AT or control group. In the AT group, CMAT was performed for 30 minutes a day for 2 months, while no intervention was provided in the control group. During the study, 2 patients from the AT group and 1 patient from the control group dropped out. At 0-, 1- and 2-month visits, results of hearing tests and speech perception tests, compliance, and questionnaires were prospectively collected and compared in the 2 groups. ResultsThe AT group (n=19) showed better improvement in word and sentence perception tests compared to the control group (n=20; PPP ConclusionsAfter using the CMAT program, word and sentence perception performance was significantly improved in experienced HA users. In addition, CMAT showed high compliance and adherence over the 2-month study period. Further investigations are needed to validate long-term efficacy in a larger population.